Interspecies determinants of Friend leukemia virus antigens involved in cytolysis of virus-pfoducing cells. - Collins, J J (1977)
The cytolytic reactivity of a complex goat anti-feline leukemia virus (FeLV) antiserum for mouse cells (Eveline) releasing large quantities of Friend leukemia virus (FLV) was analyzed by the sensitive [14C]nicotinamide release microcytotoxicity assay. Whereas this interspecies killing reactivity could be blocked by absorption of the goat anti-FeLV serum with a preparation of disrupted FLV, absorption with purified FLV gp71, the major envelope glycoprotein, had no effect. Subsequent serum absorptions with the individual FLV structural polypeptides revealed that the lysis of the Eveline cells by the goat anti-FeLV serum is mediated by antibodies recognizing the interspecies determinant of p30, the major internal capsid protein. The expression of this internal viral component at the surface of virus-producing cells is discussed further. The results also demonstrated that removal of approximately 70% of the carbohydrate portion of gp71 with a preparation of glycosidases did not affect the integrity of its interspecies determinant; these results are in agreement with an earlier study (Bolgnesi et al., 1975) that examined primarily the group- and type-specific sites.